Transformational Leadership Senior Assistant Co-curriculum: The Relationship between Perspectives and Satisfaction Among Secondary School Sports and Games Club Advisory Teachers - Nguang Ung Siong; Lau Siew Hung (Journal of Social Transformation and Regional Development, 2021)
This study was conducted to identify the relationship between the perspective and satisfaction of school sports and games club advisory teachers on the transformational leadership of Senior Assistant Co-curriculum in Secondary schools. This study is a comparative causal study and uses the Group Sampling method involving 550 secondary school teachers in Sarawak. Pearson correlation results r = .796, p <0.05 showed that there was a high and significant relationship between the transformational leadership perspective of the Senior Assistant Co-curriculum with satisfaction among secondary school sports advisory teachers. The charismatic dimension has shown the highest relationship to the satisfaction of sports club and game club advisors and is followed by the dimension of intellectual stimulation as well as inspirational motivation. The dimension of individual judgment has shown the lowest relationship to the satisfaction of sports and game club advisory teachers. Nevertheless, the dimension of individual judgment still has a high relationship with the satisfaction of sports clubs and game club advisors. Thus, transformational leadership is proposed to the Senior Assistant Co-curriculum in secondary schools because it can influence the level of satisfaction of sports club and game club advisors in the implementation of sports activities to achieve school goals and goals.